2012
DOI: 10.1016/j.jcrc.2011.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Impaired renal function is associated with greater urinary strong ion differences in critically ill patients with metabolic acidosis

Abstract: In critically ill patients with metabolic acidosis, impaired renal function was associated with greater urinary SIDs. Subsequently, the higher urinary SIDs values were related to lower pH levels, illustrating the importance of renal chloride excretion to correct for acidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…(14) In AKI patients with metabolic acidosis, there is an elevated urine SID (strong ion difference in the urine). (15) A study published in this edition of the RBTI (16) confirms this finding. It is an interesting possibility that daily monitoring of simple parameters, such as phosphorus levels, non-measurable anions and urine potassium, along with decreased urine sodium and chlorine and urine SID can facilitate the early diagnosis of AKI, even before the decrease in urinary output and creatinine.…”
mentioning
confidence: 69%
“…(14) In AKI patients with metabolic acidosis, there is an elevated urine SID (strong ion difference in the urine). (15) A study published in this edition of the RBTI (16) confirms this finding. It is an interesting possibility that daily monitoring of simple parameters, such as phosphorus levels, non-measurable anions and urine potassium, along with decreased urine sodium and chlorine and urine SID can facilitate the early diagnosis of AKI, even before the decrease in urinary output and creatinine.…”
mentioning
confidence: 69%
“…We did not separate the patients with and without pure metabolic acidosis, which could also explain, at least in part, the differences between our results and theirs. Moviat et al (9) also proposed that impaired renal function is associated with a higher SIDu in patients with metabolic acidosis. Their findings were limited by a single measurement of a simplified SIDu (NaU -ClU) per patient and a simple definition of impaired renal function, as they used an isolated creatinine measurement.…”
Section: Icu Admissionsmentioning
confidence: 99%
“…(9,11) Masevicius et al (11) reported that most of the critically ill patients with metabolic acidosis showed inappropriate renal compensation because a minority of them presented a negative SIDu. However, we believe that decreases in SIDu below the level of plasma SID (i.e., still positive values of SIDu), as occurred in most of the survivors in our study ( Figure 5), is an appropriate renal response because the majority of survivors did not meet the AKIN creatinine criteria for AKI.…”
Section: Icu Admissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired renal function is associated with greater urinary strong ion difference (SIDu) in patients with metabolic acidosis [1]. In critically ill patients, several factors, such as infused fluids and acid endogenous production, would lead to changes in plasma SID and acid-base homeostasis without renal regulation of urinary electrolytes and SIDu [2].…”
Section: Introductionmentioning
confidence: 99%